Thermal exposure induced microstructural changes and associated creep property enhancement of a PM near-α Ti–6Al–2Sn–4Zr–2Mo–0.5Y–0.5Si alloy - Xuemei Yu; Fuyang Yu; Yan Wu; Xiuzhen Zhang; Xiaogang Wu; Bowen Zhang; Hongzhi Niu; Deliang Zhang (Journal of Materials Research and Technology, 2025)
This study investigates the effects of thermal exposure on the microstructure and creep behavior of a powder metallurgy near-α Ti–6Al–2Sn–4Zr–2Mo–0.5Y–0.5Si alloy. Thermal exposure at 600 °C for 200 h induces multiple microstructural changes, including fragmentation and partial dissolution of β layers, coarsening of α lamellae, and a reduction in the fraction of low-angle grain boundaries (LAGBs). It also promotes the precipitation of nanoscale (Ti,Zr)6Si3 silicides and Ti3Al (α2), both of which follow Lifshitz–Slyozov–Wagner (LSW) coarsening kinetics. At 600 °C/250 MPa, the 200 h-exposed sample exhibits a 75 % enhancement in creep life and a 44 % reduction in steady-state creep rate compared to its counterpart without thermal exposure. This improvement in creep resistance is attributed to the synergistic effects of multiple microstructural mechanisms. Specifically, silicides promote interfacial Zener pinning and Orowan dislocation bypassing, while Ti3Al particles contribute to anti-phase boundary (APB) shear resistance. Both types of precipitates hinder dislocation motion, suppress both dynamic recovery (DRV) and dynamic recrystallization (DRX) during creep, and promote dislocation accumulation. The microstructure after thermal exposure further strengthens the dominance of the dislocation climb mechanism during the creep process. These findings provide valuable insights for optimizing the microstructure design of high-temperature near-α titanium alloys.